It's Only Rock 'n' Roll ! : Perspectives 149 - Contemporary Arts Museum, Houston (Houston : Contemporary Arts Museum Houston, 2005)
Allen, Lew ; Avedon, Richard ; Bayley, Roberta ; Benson, Harry ; Bockin, Victor ; Brodsky, Joel ; Claxton, William ; Cohen, John ; DuBose, George ; Feinstein, Barry ; Feiver, Christopher ; Freeman, Robert ; Friedlander, Lee ; Friedman, Glen ; Gassian, Claude ; Gatewood, Charles ; Goldsmith, Lynn ; Greene, Herb ; Gruen, Bob ; Hogenboom, Maurice ; Joseph, Michael ; Kane, Art ; Kirchherr, Astrid ; Kramer, Daniel ; LaChapelle, David ; Landy, Elliot ; Linn, Judy ; Malanga, Gerard ; Mankowitz, Gered ; Mapplethorpe, Robert ; Marshall, Jim ; McDarrah, Fred ; Morris, Dennis ; O'Neill, Terry ; Paulsen, Don ; Perier, Jean-Marie ; Perry, Nigel ; Pigozzi, Jean ; Resnick, Marcia ; Rock, Mick ; Russell, Ethan ; Schatt, Roy ; Schatzberg, Jerry ; Seidemann, Bob ; Seliger, Mark ; Simon, Kate ; Smith, W. Eugene ; Teller, Juergen ; Tilton, Ian ; Warhol, Andy ; Wedgebury, David ; Wentzell, Bernie ; Wertheimer, Alfred ; Whittaker, Robert
Engels
Exhibition. It's Only Rock 'n' Roll ! : Perspectives 149. Contemporary Arts Museum Houston. 2005-12-03. 2006-01-22
boek